2018
DOI: 10.1016/j.psychres.2018.05.028
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric framing affects positive but not negative schizotypy scores in psychology and medical students

Abstract: When testing risk for psychosis, we regularly rely on self-report questionnaires. Yet, the more that people know about this condition, the more they might respond defensively, in particular with regard to the more salient positive symptom dimension. In two studies, we investigated whether framing provided by questionnaire instructions might modulate responses on self-reported positive and negative schizotypy. The O-LIFE (UK study) or SPQ (New Zealand study) questionnaire was framed in either a "psychiatric", "… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 50 publications
(89 reference statements)
0
1
0
Order By: Relevance
“…This study is based on self-report questionnaires, which could represent a limit, considering that individuals with high positive schizotypy might display a tendency to respond defensively, depending on the instructions they received to answer a survey (Mohr, Schofield, Leonards, Wilson, & Grimshaw, 2018). However, this report also showed that presenting a survey as a creativity study, which is the case of our survey, minimizes defensive responses.…”
Section: Discussionmentioning
confidence: 96%
“…This study is based on self-report questionnaires, which could represent a limit, considering that individuals with high positive schizotypy might display a tendency to respond defensively, depending on the instructions they received to answer a survey (Mohr, Schofield, Leonards, Wilson, & Grimshaw, 2018). However, this report also showed that presenting a survey as a creativity study, which is the case of our survey, minimizes defensive responses.…”
Section: Discussionmentioning
confidence: 96%